1966
DOI: 10.1172/jci105387
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol-induced hemoglobinuric acute renal failure in the rat. I. Micropuncture study of the development of oliguria.

Abstract: The oliguria of acute renal failure has been attributed to tubular obstruction (1-12), "leakage" of the glomerular filtrate through rents in the tubular wall (13)(14)(15)(16)(17)(18)(19), and vascular mechanisms of various types (20)(21)(22)(23)(24)(25). In a previous paper, it was shown that the oliguria of mercury-induced acute renal failure in the rat reflects a primary decrease in glomerular filtration rate and cannot be attributed to tubular mechanisms (26). The applicability of these findings to most typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
126
4
1

Year Published

1971
1971
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(145 citation statements)
references
References 32 publications
14
126
4
1
Order By: Relevance
“…Anesthesia was induced by the intraperitoneal injection of sodium pentobarbital (50 mg/kg body weight). The animals were prepared for micropuncture studies as described previously (16). In brief, the kidney was exposed through an abdomino-flank incision, freed as gently as possible from the peri-renal fat, placed in a lucite holder, and covered with warm mineral oil.…”
Section: Methodsmentioning
confidence: 99%
“…Anesthesia was induced by the intraperitoneal injection of sodium pentobarbital (50 mg/kg body weight). The animals were prepared for micropuncture studies as described previously (16). In brief, the kidney was exposed through an abdomino-flank incision, freed as gently as possible from the peri-renal fat, placed in a lucite holder, and covered with warm mineral oil.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8] The animal model using an intramuscular glycerol injection with consequent myoglobinuria is closely related to the human syndrome of rhabdomyolysis. 9 Experimental data demonstrate renal vasoconstriction, 9-15 tubular hypoxia, 15,16 normal or even reduced intratubular pressure, [9][10][11] as well as large variation in single nephron GFR. 10,11 Intratubular myoglobin casts, a histologic hallmark, seem not to cause tubular obstruction, [9][10][11] but rather scavenge nitric oxide 17,18 and generate reactive oxygen species 19 followed by vasoconstriction.…”
mentioning
confidence: 99%
“…Recent studies on this issue (1-6) have suggested the following mechanisms leading to a reduction in measured filtration rate: (a) Renal vasoconstriction, which could decrease GFR by either a reduction in nephron plasma flow (rpf) or decrease the glomerular capillary hydrostatic pressure (Pa); (b) tubular obstruction may lead to a reduction in filtration by elevating tubular pressure and reducing the hydrostatic pressure gradient acting across the glomerular capillary membrane (AP) (4)(5)(6); and (c) transepithelial leak of solutes as large as inulin or lissamine green, as a result of epithelial injury, requiring no primary alteration in filtration at the glomerulus (7-9). The apparent disagreements which have arisen as to the exact mechanism for decreased GFR may have at least two explanations: (a) The experimental models which have been utilized differ rather markedly and (b) the experimental observations have been obtained at widely varied time intervals after the initial injury (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%